2021
DOI: 10.1155/2021/8832774
|View full text |Cite
|
Sign up to set email alerts
|

Seepage Evolution Model of the Fractured Rock Mass under High Seepage Pressure in Dam Foundation

Abstract: The seepage of the fractured rock mass in dam foundations involves complex fluid-structure coupling behavior, due to practical hydrogeological conditions. In this work, the seepage characteristics of the fractured rock mass and their correlations with the structural permeable mediums are experimentally explored to reveal the cracking effect on the hydromechanical properties firstly. Subsequently, the tangential and the compression creep damage constitutive models are, respectively, established by introducing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Therefore, both groundwater and surface water gather here. Considering the effect of artificial drainage and natural evaporation, the test rock mass gradually changes from relatively dense structure to loose irregular structure after the repeated soaking and drying cycles [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, both groundwater and surface water gather here. Considering the effect of artificial drainage and natural evaporation, the test rock mass gradually changes from relatively dense structure to loose irregular structure after the repeated soaking and drying cycles [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…ε pl min (10) where ˆ. ε pl max is the maximum value the plastic strain rate tensor, ˆ. ε pl min is the minimum value of the plastic strain rate tensor, . ε pl t is the equivalent plastic strain rate in tension, and .…”
Section: Basic Theory Of Ssd Couplingmentioning
confidence: 99%
“…analyze the sudden pipeline crash of a specific project and derive its evolution process. Zhao et al [10] proposed an innovative permeability evolution equation. They found that the seepage pressure will continuously intensify fracture propagation and penetration in the rock mass due to the time effect of permeability and failure.…”
Section: Introductionmentioning
confidence: 99%
“…In many types of geological projects, such as the prevention and control of groundwater pollution [1,2] and seepage in a dam foundation [3,4], the contact deformation and development of mass fractures under in situ stress leads to sewage infiltration, and the collapse of the dam foundation is the key factor affecting the project. Therefore, fracture contact and seepage in rocks are the focus of engineering stability studies.…”
Section: Introductionmentioning
confidence: 99%